2001
DOI: 10.1177/146045820100700203
|View full text |Cite
|
Sign up to set email alerts
|

An informaticist working in primary care: a descriptive study

Abstract: A regional R and D grant was used to explore how an informaticist could stimulate and respond to questioning behaviour in primary care clinicians. Training needs for the informaticist were identified and provided for. Nurses and doctors working in primary care were approached individually. They were encouraged to think about their clinical behaviour and to identify topics where they thought they might like to have more evidence either to justify their current practice or to stimulate change. The personal appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The quantity and nature of the questions in the two projects are available as separate reports 10 11 and are summarised in the table on bmj.com. Both project groups found that relatively few primary care staff spontaneously submitted questions to the service.…”
Section: Resultsmentioning
confidence: 99%
“…The quantity and nature of the questions in the two projects are available as separate reports 10 11 and are summarised in the table on bmj.com. Both project groups found that relatively few primary care staff spontaneously submitted questions to the service.…”
Section: Resultsmentioning
confidence: 99%
“…The literature was reviewed for similar librarian consultation services to see if we could learn from others. Similar services were found both within and outside the library context, using either a clinical question and answer (Q&A) service [4][5][6][7][8][9][10][11] or virtual reference service. 12,13 All of the Q&A services were in primary care and while the virtual reference services included all types of health specialties.…”
Section: Design Requirements and Review Of Existing Evidencementioning
confidence: 99%
“…While the Imperial project was running, a parallel service was being provided from a GP practice in Basildon, a town in the south‐east of England 29 . Although, in principle, the services were similar, and in each case the informaticist was a GP, the projects evolved in different ways.…”
Section: Clinical Informaticist Servicesmentioning
confidence: 99%
“…While the Imperial project was running, a parallel service was being provided from a GP practice in Basildon, a town in the south-east of England. 29 Although, in principle, the services were similar, and in each case the informaticist was a GP, the projects evolved in different ways. The emphasis in the Imperial project was academically orientated, whilst that of the Basildon project was service orientated-conceptualized as a 'friendly local facilitator' rather than a 'laboratory testing service'.…”
Section: Clinical Informaticist Servicesmentioning
confidence: 99%
See 1 more Smart Citation